Correlation between Hematocrit and Platelet Counts in Dengue Hemorrhagic Fever Patients: A Study at Emanuel Hospital, Banjarnegara - Pancawati, Yulina; Pangesti, Ira; Nugroho, Yusuf Eko (Journal of Indonesian Medical Laboratory and Science, 2025)
Background: Dengue Hemorrhagic Fever (DHF) is an infectious disease caused by the dengue virus and transmitted by Aedes aegypti mosquitoes. Without prompt management, DHF can lead to severe complications and death. The World Health Organization (WHO) identifies thrombocytopenia and increased hematocrit as key diagnostic parameters for DHF. Objectives: This study aimed to assess the correlation between hematocrit levels and platelet counts in patients with Dengue Hemorrhagic Fever at Emanuel Hospital, Banjarnegara. Materials and Methods: This cross-sectional study used secondary data from the hospital’s Electronic Medical Records (EMR) and Laboratory Information System (LIS). Statistical analysis was performed using Pearson’s correlation test. Results: The analysis showed a significant negative correlation between hematocrit and platelet counts in DHF patients (r = –0.760, p < 0.001). Conclusions: The findings indicate that an increase in hematocrit is associated with a decrease in platelet counts, emphasizing the importance of simultaneous monitoring of both parameters in the clinical management of DHF. This study contributes to local epidemiological data and underscores the potential of these laboratory indicators as practical tools for assessing disease severity.